G C MOTOR – AN AUTOMATION MODULE TO IMPROVE LIFESTYLE - Mannickathan, Kiron MD; Sairam S; Babu, Shimil S; Jubilant J Kizhakkethottam (International Journal of Psychosocial Rehabilitation, 2020)
The gesture-controlled motor is a technology to control motor-based equipment with gestures. Gestures can be hand gesture or movements of any body parts. This technology will help the people to control their equipment easily with gestures. The gestures are recognized by optical cameras placed at different angles. For old aged people, children, it is difficult to manage any equipment which is at a higher altitude. Hence, they need some methods to overcome this situation. GC Motor helps them to control the equipment as they need. For differently able people, it is difficult to control the equipment which are far away. So, GC Motor will help to control the equipment with gestures without going near to them. The GC Motor help common people to improve their daily life. Any equipment driven by motor can be controlled with gesture. In a faster growing world, where the new technologies are developing day by day, and the people are attractive towards those technologies to simplify their life too. GC Motor is a new technology that can make life simpler and more luxurious. This technology has a wide range of application. For home automation, using GC Motor we can control doors, windows, curtains, etc.